ANALYSIS STUDY ON STUDENTS’ ABILITY IN USING REFERENCE IN READING NARRATIVE TEXT AT FOURTH SEMESTER STUDENTS OF STIBA PERSADA BUNDA PEKANBARU - Maspufah Maspufah (Universitas Pahlawan Tuanku Tambusai, 2016)
Reference is one component for comprehending a reading text. This research employed descriptive method. The purpose of the research was to find out the students’ ability in using reference in reading narrative text. The subject of the research was twenty two students of fourth semester of 2015/2016 STIBA Persada Bunda Pekanbaru. The instrument used to collect the data was in the form of multiple tests. From the finding, it was found that: (1) The students’ ability in using personal reference was in good category. They had problems in mastering personal reference which refers forward or cataphora reference (2) the students’ ability in using demonstratives reference in narrative texts was in good category. The problems occurred because they had limited vocabulary and lack of motivation. Thus, it can be concluded that the students’ ability in using reference in narrative text still needed to be improved because they still had limited vocabulary and lack of motivation.